Use of Validated Questionnaires to Predict Cosmetic Outcomes of Hypospadias Repair - Amos Neheman; Omri Schwarztuch Gildor; Andrew Shumaker; Ilia Beberashvili; Yuval Bar-Yosef; Shmuel Arnon; Amnon Zisman; Kobi Stav (MDPI AG, 2024)
Introduction: Hypospadias is a syndrome of penile maldevelopment. The primary goal of hypospadias surgery is to create a penis with normal appearance and function. Historically, the outcome of hypospadias repair has been assessed based on the need for reoperation due to urethroplasty complications (UC), including fistula formation, dehiscence, meatal stenosis, or development of a urethral stricture. The Glans-Urethral Meatus-Shaft (GMS) score is a standardized tool to predict UC. Analysis of the cosmetic outcomes of hypospadias repair based on the appearance of the reconstructed penis has been validated, and standardized scores have been published. The Hypospadias Objective Penile Evaluation (HOPE) score is a validated questionnaire used to assess postoperative cosmetic outcomes. Although predictors of surgical outcomes and UC have been well documented, predictors of optimal cosmetic outcomes are lacking in the literature. Furthermore, reoperation due to cosmetic considerations has been poorly reported. Objective: To identify predictors of cosmetic outcomes after hypospadias repair and to assess the reoperation rate according to cosmetic considerations. Materials and Methods: This prospective cohort study included 126 boys who underwent primary hypospadias repair. The severity of hypospadias, degree of penile curvature, glans width, preoperative HOPE, and GMS scores were documented. The standard technique for single-stage repairs, the tubularized incised plate urethroplasty, was performed. The primary endpoint was cosmetic outcomes evaluated by the HOPE score questionnaire six months postoperatively. Optimal cosmetic results were defined by HOPE scores ≥ 57. Results: The study population consisted of the following cases: 87 (69%) subcoronal, 32 (25%) shaft, and 7 (6%) proximal hypospadias. Among the study participants, 102 boys (81%) had optimal cosmetic results (HOPE ≥ 57), and 24 boys (19%) had surgeries with suboptimal cosmetic outcomes (HOPE < 57). Ancillary procedures were performed in 21 boys (16%), of which 14 (11%) were solely for cosmetic considerations, and 7 were secondary to UC. Using the Receiver Operating Characteristic analysis of potential predictors of optimal cosmetic outcomes, the preoperative HOPE score had the highest area under the curve (AUC = 0.79; 95% CI 0.69-0.89, p < 0.001). After multivariable analysis, the degree of penile chordee (p = 0.013), glans width (p = 0.003), GMS score (p = 0.007), and preoperative HOPE score (p = 0.002) were significant predictors of cosmetic outcomes. Although meatal location predicted suboptimal cosmetic results in univariate analysis, it was not a factor in multivariable analysis. Conclusions: Over 80% of boys undergoing hypospadias repair achieved optimal cosmetic outcomes. More than 10% of cases underwent ancillary procedures, secondary solely to cosmetic considerations. Predictors of optimal cosmetic outcomes after hypospadias surgery included degree of chordee, glans width, and preoperative HOPE and GMS scores, which were the best predictors of satisfactory cosmetic results. Although meatal location is the main predictor of UC, it was not a predictor for cosmetic outcomes. Factors affecting cosmetic outcomes should be clearly explained to parents during the preoperative consultation.